The spreading of Cāṇakya's aphorisms over "Greater India" - Sternbach, Ludwik (Calcutta Oriental Book Agency, 1969)
On the appearance maxims attributed to Kautalya, 4th cent. B.C., in the literatures of South and South East Asia.